2013
DOI: 10.1002/pbc.24776
|View full text |Cite
|
Sign up to set email alerts
|

PedsQL™ multidimensional fatigue scale in sickle cell disease: Feasibility, reliability, and validity

Abstract: Background Sickle cell disease (SCD) is an inherited blood disorder characterized by a chronic hemolytic anemia that can contribute to fatigue and global cognitive impairment in patients. The study objective was to report on the feasibility, reliability, and validity of the PedsQL™ Multidimensional Fatigue Scale in SCD for pediatric patient self-report ages 5–18 years and parent proxy-report for ages 2–18 years. Procedure This was a cross-sectional multi-site study whereby 240 pediatric patients with SCD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
65
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 46 publications
7
65
0
1
Order By: Relevance
“…25,28 The PedsQL generic core scales and the PedsQL multidimensional fatigue scales, which are valid and reliable for use in patients with sickle cell disease, were used to assess HRQL with the resultant total HRQL scores. 29,30 The PedsQL sickle cell disease module, the only valid and reliable disease-specific measure for children with sickle cell disease, was also used. 31 HRQL assessments were measured at all 8 sites by paper report (parent proxy for all patients 18 years old or younger, self-report for patients 8 years old or older, and self-report with aid of the research coordinator for patients aged 5-7 years) before the first study drug infusion, after the sixth dose of medication (or immediately before discharge if fewer than 6 doses were administered), and by telephone 8 to 10 days postdischarge.…”
Section: Study Outcomesmentioning
confidence: 99%
“…25,28 The PedsQL generic core scales and the PedsQL multidimensional fatigue scales, which are valid and reliable for use in patients with sickle cell disease, were used to assess HRQL with the resultant total HRQL scores. 29,30 The PedsQL sickle cell disease module, the only valid and reliable disease-specific measure for children with sickle cell disease, was also used. 31 HRQL assessments were measured at all 8 sites by paper report (parent proxy for all patients 18 years old or younger, self-report for patients 8 years old or older, and self-report with aid of the research coordinator for patients aged 5-7 years) before the first study drug infusion, after the sixth dose of medication (or immediately before discharge if fewer than 6 doses were administered), and by telephone 8 to 10 days postdischarge.…”
Section: Study Outcomesmentioning
confidence: 99%
“…However, there is evidence from factor analysis that both instruments are explained by 3 to 4 factors. 79,80,122 Studies beyond the scope of this review further suggest multiple factors in fatigue assessment instruments, with recent evidence confirming a 3-factor structure of the PedsQL MFS, 134 and a 2-factor structure of the PROMIS scale. 2 The field of research is yet to develop a coherent way of relating this emerging evidence regarding fatigue dimensionality with quantification of symptoms.…”
Section: Discussionmentioning
confidence: 57%
“…Finally, the authors showed clinical potential and focusing the scale research of purposes to assess the severity of symptoms of fatigue [10] and said that the use of it will facilitate the understanding of health and wellbeing of children with the disease [9]. In Portugal, a version of PedsQL was also validated to be applied to children aged between 5-7 years old and 8-12 years old diagnosed with diabetes mellitus type 1 or spina bifida [8].…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis build of the selected studies in the review show that the motivation to develop an instrument or quiz in the theme of chronical is strictly linked to factors, as: handling of a specific disease such as diabetes [6,7,8], sickle cell anemia [9,10], asthma [7,11,12], chronic kidney disease [13], Cystic fibrosis [14]; children and/or adolescents family inclusion in the validation process or as subject of the instrument application [6,10,15,16,17]; measurement of subjective dimensions of life experience with chronic disease such as: quality of life [7,13], satisfaction with care [17], chronic pain experience [18] as well as the limitations to develop common activities [19]. The use of statistical measures as tools to support the validity, reliability and reproducibility of instruments built was present in all studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation